ANALISIS CAMEL RATIO PADA BANK BUMN UNTUK MENILAI KINERJA DAN RESIKO PENGELOLAAN KEKAYAAN NEGARA DIPISAHKAN (KND) - Dina Amaluis (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2023)
The study aims to measure the performance of management/health of state-owned banks using the CAMEL Ratio. State-owned banks in Indonesia have a very significant role in the Indonesian economy. The role of State Own Banks in general in the national economy is to help the development of small, micro, and medium enterprises (UMKM), as well as cooperatives. State-owned banks obtain sources of funds from Segregated State Wealth (KND). This research uses the Quantitative Descriptive method using data from state-owned banks listed on the Indonesia Stock Exchange during 2017 to 2021. The results of the analysis show that four the state-owned banks listed Bank Mandiri, Bank BNI, Bank BRI dan Bank Tabungan Negara throughout the study period have good CAR, NPL, and LDR values so that they can be declared state-owned banks are Health. CAMELs Ratio analysis that can measure the health performance of state-owned banks can be a measurement item for State Own managers who use an Early Warning System.